Risks for Scaling Up Nutrition in Senegal - Ba, Babacar (World Bank, Washington, DC, 2019)
Senegal has one of the most effective and comprehensive nutrition service delivery systemsin Africa. Between 1991–92 and 2012–13, chronic malnutrition dropped from 34.4 percent to lessthan 20 percent. However, this progress has not led to stepped up nutrition-sensitive interventions in relevant sectors such as agriculture, education, water and sanitation, social protection, or health. This absence of nutrition-sensitive interventions, combined with aseries of external shocks (economic crises, increased food prices, and irregular rainfall), has resulted in a persistent fragmentation of approaches, discourse,and interventions. As a result, there is no comprehensive framework guiding nutrition investments in Senegal.